COHERENCE STRATEGIES AND DEVICES IN EFL ACADEMIC WRITING INTRODUCTIONS - Vincentia Sri Harti Siswanti; Ignatius Harjanto (Magister Scientiae, 2018)
The study was intended to describe the coherence strategies and devices used by the graduate students of Widya Mandala Catholic University Surabaya in writing Introduction section to achieve coherence. This discourse analysis study described the internal relationship of form and meaning by applying textual analysis with a multimodal analysis. The researcher found non-deductive and neither deductive nor non-deductive strategy in this study. The non-deductive strategy consisted of three elements: context establishment, further focus, and thesis statement. The neither deductive nor non-deductive strategy did not have any complete elements, so those writings were categorized as incoherent introductions. Beside those strategies, there were 6 coherence devices identified; they were repetition of key nouns, the definite article ‘the’, parallelism, purpose signals, substitution, and transitional signals.